Study on the intervention effect of mindfulness-based stress reduction on postoperative cognitive dysfunction and psychological resilience in lung cancer patients - Ji, Xiaona; Ding, Haiyan; Meng, Yingtao (Frontiers in Neurology, 2025)
BackgroundPostoperative cognitive dysfunction and psychological problems seriously affect the quality of life and recovery of lung cancer patients. As an emerging psychological intervention method, mindfulness-based stress reduction (MBSR) has been widely recognized and applied in the medical field.ObjectivesEvaluating the effectiveness of MBSR as an intervention for postoperative cognitive dysfunction and psychological resilience in lung cancer patients.MethodsA total of 86 patients who underwent lung cancer surgery in our hospital from January 2022 to December 2023 were enrolled in this study. The research subjects were divided into the control group and the research group by using the method of random number table, each with 43 cases. The control group used conventional care, while the research group used mindfulness-based stress reduction. Differences in outcome indicators between the two groups were assessed through the relevant assessment tools, with statistically significant differences defined as a p-value of < 0.05.ResultsBefore the intervention, there were no significant differences in cognitive functioning, psychological resilience, self-efficacy, cancer-induced fatigue, and sleep quality scores between the two groups (p > 0.05). After 8 weeks of intervention, Montreal Cognitive Assessment (MoCA), Connor-Davidson Resilience Scale (CD-RISC), and General Self-Efficacy Scale (GSES) scores were elevated in both groups, and in the research group, the MoCA scores (26.23 ± 1.45 vs. 25.05 ± 1.17, p < 0.001), the CD-RISC total score (66.26 ± 8.27 vs. 61.79 ± 7.93, p = 0.012), and GSES score (30.19 ± 3.27 vs. 26.37 ± 2.31, p < 0.001) were significantly higher than those of the control group. In addition, Piper Fatigue Scale score (PFS) and Pittsburgh Sleep Quality Index (PSQI) scores decreased in both groups after the intervention. Behavioral fatigue (4.02 ± 1.28 vs. 4.61 ± 1.37, p = 0.045), emotional fatigue (3.28 ± 1.39 vs. 3.93 ± 1.40, p = 0.033), somatic fatigue (3.81 ± 1.30 vs. 4.47 ± 1.37, p = 0.026), and cognitive fatigue (4.07 ± 1.39 vs. 4.72 ± 1.37, p = 0.031) were significantly lower in the research group than in those in the control group, as was the total sleep quality score (8.63 ± 1.59 vs. 11.12 ± 1.31, p < 0.001).ConclusionMBSR can effectively improve postoperative cognitive function, enhance psychological resilience, and alleviate cancer-induced fatigue, and sleep disorders in lung cancer patients.